2013
DOI: 10.1103/physrevb.87.085301
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation properties of acoustic phonons generated by ultrafast optical excitation of a quantum dot

Abstract: We study theoretically the fluctuation properties of acoustic phonons created in a semiconductor quantum dot after ultrafast optical excitation. An excitation with a single ultrafast pulse creates an exciton confined to the quantum dot, which is coupled to longitudinal acoustic phonons. This leads to the formation of a polaron in the quantum dot accompanied by the emission of a phonon wave packet. We show that the fluctuations of the lattice displacement associated with the wave packet after a single laser pul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
(50 reference statements)
3
22
0
Order By: Relevance
“…We found that the excited electronic distribution efficiently couples to acoustic phonons through the deformation potential (DP) mechanism. In agreement with previous theoretical calculations, 43–45 we interpret our observations as a result of a nonequilibrium phonon population composed of two parts: one localized within the dots, as detected from the Bragg reflections, and one traveling at the speed of sound in the surrounding region as a phonon wavepacket (WP), as retrieved from the dynamics of surface wave resonance (SWR) features.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the excited electronic distribution efficiently couples to acoustic phonons through the deformation potential (DP) mechanism. In agreement with previous theoretical calculations, 43–45 we interpret our observations as a result of a nonequilibrium phonon population composed of two parts: one localized within the dots, as detected from the Bragg reflections, and one traveling at the speed of sound in the surrounding region as a phonon wavepacket (WP), as retrieved from the dynamics of surface wave resonance (SWR) features.…”
Section: Introductionsupporting
confidence: 91%
“…This is contrary to our experimental observations, where a time constant of 2.5–4 ps is measured and can rather be interpreted according to the following scenario. It has been theoretically predicted 43–45 that the deformation potential mechanism responsible for the excitation of acoustic phonons within the dots is associated to the buildup of a nonequilibrium phonon distribution consisting of two parts: a localized one that remains within the dots and reflects the polaronic nature of the excited state, as discussed above, and another part that, because of the spatial dispersion of the acoustic phonons, leaves the dot and propagates in the surrounding regions as a phonon wavepacket (WP) travelling at the speed of sound. In this scenario, the time necessary for the travelling wave to leave the dot and propagate in the surrounding substrate can be estimated as τWP=h/vA,where h is the dot height and vA is the acoustic phonon speed.…”
Section: Ultrafast Phonon Dynamicsmentioning
confidence: 95%
“…42,43 For this case, it has been found that by the impulsive excitation a lattice deformation in the region of the QD is created forming the acoustic polaron, which is accompanied by the emission of a phononic wave packet. [42][43][44][45][46] By excitation with a tailored series of pulses the fluctuations of the phonons can be modified such that squeezed phonon wave packets can be generated. 43 In the case of excitation by sufficiently slowly varying light fields, on the other hand, the polaron builds up adiabatically and no phonon wave packet is emitted.…”
Section: -20mentioning
confidence: 99%
“…[42][43][44][45][46] By excitation with a tailored series of pulses the fluctuations of the phonons can be modified such that squeezed phonon wave packets can be generated. 43 In the case of excitation by sufficiently slowly varying light fields, on the other hand, the polaron builds up adiabatically and no phonon wave packet is emitted.…”
Section: -20mentioning
confidence: 99%
See 1 more Smart Citation